2009
DOI: 10.1016/j.exer.2008.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial function and redox control in the aging eye: Role of MsrA and other repair systems in cataract and macular degenerations

Abstract: Oxidative stress occurs when the level of prooxidants exceeds the level of antioxidants in cells resulting in oxidation of cellular components and consequent loss of cellular function. Oxidative stress is implicated in wide range of age related disorders including Alzheimer's disease, Parkinson's disease amyotrophic lateral sclerosis (ALS), Huntington's disease and the aging process itself (Lin and Beal, 2006). In the anterior segment of the eye, oxidative stress has been linked to lens cataract (Truscott, 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
141
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(149 citation statements)
references
References 94 publications
2
141
0
5
Order By: Relevance
“…These are associated with progressive damage to the pigment cells of the substantial nigra midbrain: cells which are responsible for the synthesis of dopamine under physiological conditions, which they use as a neurotransmitter [44,45,46,47,48,49]. Patients with Alzheimer's and Parkinson's disease are more likely to suffer from glaucoma than healthy people, and severe adverse reactions location biochemical, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…These are associated with progressive damage to the pigment cells of the substantial nigra midbrain: cells which are responsible for the synthesis of dopamine under physiological conditions, which they use as a neurotransmitter [44,45,46,47,48,49]. Patients with Alzheimer's and Parkinson's disease are more likely to suffer from glaucoma than healthy people, and severe adverse reactions location biochemical, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, age-related cataract (ARC) is a pathological lesion that occurs with aging in humans, other mammals, and birds (Slatter et al 1983;Williams et al 2004;Wolf et al 2005;Zubenko et al 2007) and is at least partly linked to lens oxidative damage (Davies 1995;Spector 1995;Reddy et al 2001;Wolf et al 2005;Pendergrass et al 2006;Brennan and Kantorow 2009). We previously have shown a correlation between longevity in human nonagenarians and their delay in developing ARC (Zubenko et al 2007), and also demonstrated that small GH-R, IGF-1 deficient mutant dwarf mice have both delayed ARC development and extended life spans (Wolf et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Lens researchers generally consider that age-related cataracts (ARCs) are strongly associated with lens oxidation and aging (16)(17)(18). Although a direct association between cataract …”
Section: Discussionmentioning
confidence: 99%